The relationship between raising a child with a disability and the mental health of mothers compared to raising a child without disability in japan - Yui Yamaoka; Nanako Tamiya; Nobuyuki Izumida; Akira Kawamura; Hideto Takahashi; Haruko Noguchi (Elsevier, 2016)
Objective: Previous studies conducted in Japan targeted only mothers who cared for children with disabilities, and lacked reference subjects, such as mothers of children without disabilities. The aim of this study was to examine the association between raising one or two children with a disability and maternal psychological distress compared to mothers of children without a disability, and to assess differences among partnered mothers living with grandparent(s), partnered mothers without grandparent(s), and single mothers. Methods: This study utilized data from the Comprehensive Survey of Living Conditions (CSLC) in 2010. We merged the data of the children (aged six and over), mothers, and fathers. This study obtained 33,739 study subjects as a triad of a child (33,110 children without disabilities and 629 children with disabilities), mother, and father. The Japanese version of Kessler 6 (K6) was used to assess the psychological distress of mothers. Multivariate logistic regression was performed to assess the independent association of a child with a disability on maternal psychological distress after controlling for the basic characteristics of the children, mothers, and households. Results: This study reported that raising one or two children with disabilities was significantly related to maternal psychological distress (odds ratio: 1.72 for one child, 2.85 for two children) compared to mothers of children without disability. After stratifying the analyses by family structure, significant associations remained among mothers in two-parent families but not for mothers in three-generation families and single mothers due to a small number of children with disabilities in these families. Conclusions: This study reported the significant association between raising a child with a disability and maternal psychological distress in comparison to mothers of children without disabilities. Attention should be paid to not only single mothers, but also partnered mothers in two-parent families who have a child with a disability. It is important for health professionals to focus on the mental health of every mother of a child with a disability and to assess their needs for psychological support. Keywords: Children with disabilities, Mothers, Psychological distress, Family structure, Japan